2015
DOI: 10.3727/096368914x683548
|View full text |Cite
|
Sign up to set email alerts
|

Human Pancreatic Islets Isolated from Donors with Elevated HbA1c Levels: Islet Yield and Graft Efficacy

Abstract: 0.09 ± 0.01 and 0.21 ± 0.03 nmol O2 100 islets(-1) min(-1), p = 0.049). The islets isolated from T2D donor pancreata reversed diabetes in NOD-SCID mice in 9% (2/22) compared to islets from control donor pancreata, which reversed diabetes in 67% (175/260, p < 0.001). In conclusion, this study demonstrates that elevated HbA1c (≥ 6.5%) is associated with impairment of islet function and lower islet yield; however, these islets could not be suitable for clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…HbA1c > 6.5% suggests the donor suffered from diabetes. It has been reported that islets isolated from type 2 diabetic donor pancreas had impairment of islet function and lower islet yield (28). …”
Section: Discussionmentioning
confidence: 99%
“…HbA1c > 6.5% suggests the donor suffered from diabetes. It has been reported that islets isolated from type 2 diabetic donor pancreas had impairment of islet function and lower islet yield (28). …”
Section: Discussionmentioning
confidence: 99%
“…Primary human pancreatic acini were obtained from pancreatic cadaveric tissues from organ donors as we recently reported (Lugea et al 2017b). Briefly, pancreata were digested at the City of Hope National Medical Center (Duarte, CA, USA) to separate islets from ductal-acinar trees as previously described (Qi et al 2015). The resulting acini were transferred to Cedars-Sinai Medical Center facilities (Los Angeles, CA, USA) and cultured as indicated above for rodent pancreatic acini.…”
Section: Isolation Of Mouse Rat and Human Pancreatic Acinimentioning
confidence: 99%
“…Primary human pancreatic acini were obtained from cadaveric pancreatic tissues from organ donors. Briefly, pancreata were digested at City of Hope (Duarte, CA, United States) to separate islets from acinoductal trees, as described (Qi et al, 2015). The resulting acini were transferred to Cedars-Sinai Medical Center (Los Angeles, CA, United States) and further prepared and characterized as previously described (Lugea et al, 2017).…”
Section: Methodsmentioning
confidence: 99%